2014
DOI: 10.1097/ede.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Telomere Length and Age at Menopause

Abstract: Background Telomere length is a marker of cellular aging that varies by the individual, is inherited, and is highly correlated across somatic cell types within persons. Inter-individual telomere length variability may partly explain differences in reproductive aging rates. We examined whether leukocyte telomere length was associated with menopausal age. Methods We evaluated the relationship between leukocyte telomere length and age at natural menopause in 486 white women aged 65 years or older. We fit linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…In accordance with animal studies, post-menopausal women aged 55 to 69 who were on a long-term hormone therapy regimen (more than five years of 0.625 mg of CEE or 2 mg of 17β-estradiol with a progestin component) had longer telomeres than post-menopausal women within the same age range who had never been exposed to exogenous hormone therapy after menopause (Lee et al, 2005), and correlations have been reported between maternal estriol levels during pregnancy and their infant's telomere length (Entringer et al, 2014). Other research has shown that women with longer telomeres were older at the time of natural menopause, while women who underwent surgical menopause showed no associations between age at menopause and telomere length (Gray et al, 2014), and that women who experienced premature ovarian failure tended to have longer telomeres compared to control participants (Hanna et al, 2009). Of note, especially lending biological support to the previously discussed idea that older fathers positively impact the lifespan of children, a positive correlation between paternal age when an infant is born and telomere length in that child has been noted (Kuhle, 2007; Prescott et al, 2012).…”
Section: Menopause: Etiology Evolution and Estrogensmentioning
confidence: 97%
“…In accordance with animal studies, post-menopausal women aged 55 to 69 who were on a long-term hormone therapy regimen (more than five years of 0.625 mg of CEE or 2 mg of 17β-estradiol with a progestin component) had longer telomeres than post-menopausal women within the same age range who had never been exposed to exogenous hormone therapy after menopause (Lee et al, 2005), and correlations have been reported between maternal estriol levels during pregnancy and their infant's telomere length (Entringer et al, 2014). Other research has shown that women with longer telomeres were older at the time of natural menopause, while women who underwent surgical menopause showed no associations between age at menopause and telomere length (Gray et al, 2014), and that women who experienced premature ovarian failure tended to have longer telomeres compared to control participants (Hanna et al, 2009). Of note, especially lending biological support to the previously discussed idea that older fathers positively impact the lifespan of children, a positive correlation between paternal age when an infant is born and telomere length in that child has been noted (Kuhle, 2007; Prescott et al, 2012).…”
Section: Menopause: Etiology Evolution and Estrogensmentioning
confidence: 97%
“…Specifically, there is an estrogen receptor response element on the telomerase gene promoter and estrogen has been shown to increase both telomerase expression and activity (Kyo and others 1999; Misiti and others 2000; Nanni and others 2002). Indeed, previous studies indicate that a later onset of menopause and longer exposure to circulating estrogen is associated with greater leukocyte telomere length in women (Gray and others 2014; Lin and others 2011). However, although we confirm a decline in mean telomere length with age in arteries, we did not find a sex specific difference in mean arterial telomere length.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of sex differences related to telomeres have typically focused on only telomere length in circulating immune cells, with most studies indicating that women have longer telomeres than men in leukocytes (Bekaert and others 2007; Fitzpatrick and others 2011; Gardner and others 2014; Willeit and others 2010). In addition, later onset of menopause and longer exposure to circulating estrogen is associated with greater leukocyte telomere length in women (Gray and others 2014; Lin and others 2011). Thus, not only is it unknown if telomere uncapping or mean telomere length are different in the arteries of women and men, but the role of menopause in women has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among Mexican-American women, one standard deviation in shorter leukocyte telomere length was associated with a 1.56 year earlier age at menopause; and among non-Hispanic black women, no association was found (57). Another study with a cohort of 486 white women found that for every 1 kilobase increase in leukocyte telomere length, average age at natural menopause increased by 10.2 months (95% CI: 1.3–19.0), with no association seen in women with surgical menopause (58). …”
Section: Menopausementioning
confidence: 99%
“…Nitrites can come from degradation of some cosmetic preservatives when they are exposed to air (57) and nitrites are sometimes used in cosmetics as anti-corrosive ingredients (58). …”
Section: Figurementioning
confidence: 99%